Audit Operasional atas Fungsi Penjualan PT. Gaya Makmur Surabaya - Nanda Kartikasari; Nur Lailiyatul Inayah (Equity: Jurnal Akuntansi, 2023)
The purpose of this research is to understand the process by which the sales function carrying out the operational activities of PT. Gaya Makmur Surabaya, as well as detecting and provide recommendations about weaknesses in the operation of the sales function. Approach used is descriptive qualitative. Data collection methods in this study includes observation, interviews, checklists, and documentation. Research result concluded that overall PT. Gaya Makmur Surabaya has run sales function in accordance with applicable regulations. However, it still exists cases where some of the company's activities do not go according to procedure. Control internal company related to the sales function is considered efficient and effective, but still there are several weaknesses such as inaccurate recording of accounts receivable, billing, and late payments by irregular customers. If it continues, then the company experience loss.